Capacity Increase Plan Analysis by Adding Lane to the Jakarta-Cikampek Toll Road - Desti Anggraeni (Green Publisher Indonesia, 2024)
The Jakarta-Cikampek Toll Road serves as a vital route, connecting Jakarta to its eastern suburbs and facilitating both passenger travel and logistics operations. However, persistent congestion along this stretch of highway has prompted the need for a comprehensive assessment of its capacity performance. This study aims to evaluate the Jakarta-Cikampek Toll Road's capacity performance using the V/C ratio metric. The analysis encompasses the calculation of V/C ratio values for the years 2022–2023, forecasting peak-hour daily traffic volumes for 2024 under three distinct scenarios: (i) no capacity expansion, (ii) capacity expansion through the addition of one lane, and (iii) traffic management intervention involving one-lane contraflow. The findings reveal that the highest V/C ratio values for peak hours in 2024, without lane additions, are 0.65 for Lane A and 0.71 for Lane B. However, these values decrease to 0.49 for Lane A and 0.53 for Lane B when considering capacity expansion through lane addition or contraflow implementation. Therefore, to ensure compliance with the Minimum Service Standards (SPM) until the end of the concession period, it is recommended that the toll road operator implement capacity enhancement by adding one lane in each route.